PECULIARITIES OF DEMODECOSIS COURSE IN HELMINTHOSES ASSOCIATIONS OF DOGS’ DIGESTIVE TRACT - Yevstafieva, V. О.; Lychman, A. S. (Scientific Progress & Innovations, 2020)
Demodecosis invasion occupies a particular place among the diseases of pets. Most often dogs are affect- ed by the disease and it can cause considerable economic losses to dog breeding. At the same time, de- modecosis has social importance, as dogs constantly contact with their owners. Demodecosis is widely spread in many European countries including Ukraine, where the invasion tends to constant spreading as a result of increasing the number of carnivorous animals, especially in cities and towns. The studies were con- ducted in the laboratory of the Department of Parasitology and Veterinary-Sanitary Expert Examination of Poltava State Agrarian Academy. The aim of the research was to investigate the peculiarities of demodecosis course in the helminthoses of dog digestive tract and determine the main associates of mixed invasions. Dogs’ skin scrapings studies were conducted by vital method. Helminth oovoscopy of dogs’ feces samples infected with Demodex canis was made by Kotelnikov-Khrenov’s method. According to the results of dogs’ acarological studies, it was established that the average prevalence of demodecosis invasion made 21.43 % among the animal skin pathologies in the town of Poltava. Mixed invasions were presented by two- component and three-component associations of parasites, namely: Demodex canis (Leydig, 1859), Trichuris vulpis (Frцlich, 1789), and Uncinaria stenocephala (Railliet, 1884), in different combinations. Most often, demodecosis-trichurosis invasion was detected (54.55 of all the revealed mixed invasions). Demodecosis- uncinariosis (27.27 %) and demodecosis-trichurosis-uncinariosis (18.18 %) invasions were registered less frequently. It was determined that demodecosis was manifested both as mono-invasion in infected dogs (47.62 %) and association with intestinal nematodoses (52.38 %). Two-component mixed invasions dominat- ed, in which the indices of prevalence reached 42.86 %. Three-component invasion was revealed only in 9.52 % of dogs diseased with demodecosis. The obtained results of studies supplement the existing data as to the course of dog demodecosis and will also enable to conduct complex treatment of demodecosis associative course.